Isoorientin Attenuated the Pyroptotic Hepatocyte Damage Induced by Benzo[a]pyrene via ROS/NF-κB/NLRP3/Caspase-1 Signaling Pathway - Hao Li; Li Yuan; Xueyi Li; Ying Luo; Zhong Zhang; Jianke Li (MDPI AG, 2021)
Isoorientin (Iso), a natural bioactive flavonoid, possesses significant anti-tumor and anti-oxidant activities. Benzo[a]pyrene (BaP) is a food processing injurant with carcinogenicity, teratogenicity, and genotoxicity. Our preliminary study demonstrates that Iso attenuated the pyroptotic hepatocyte damage induced by BaP; however, the molecular mechanism remains unknown. The present study showed that Iso reduced the increase caused by BaP in the overflow of LDH, NO, and the electrical conductivity and the protein expressions of GSDMD-N, IL-18, and IL-1β, further showing that Iso could reduced the pyroptotic damage in HL-7702 cells induced by BaP. Caspase-1 inhibitor (Z-VAD-FMK) inhibited the characteristic pyroptosis protein expressions of Caspase-1, GSDMD-N, IL-18, and IL-1β, showing that the classic pyroptosis pathway depending on Caspase-1 was caused by BaP in HL-7702 cells. Consistent with the effects of the NLRP3 inhibitor (MCC950), NF-κB inhibitor (PDTC), ROS, and mtROS inhibitor (NAC and Mito-TEMPO), Iso weakened the stimulatory effects of BaP on the levels of ROS, the nuclear localization of NF-κB, and the activation of NLRP3 inflammasome and the characteristic indices of pyroptosis, demonstrating that Iso could alleviate the BaP-induced pyroptotic hepatocytes injury through inhibiting the ROS/NF-κB/NLRP3/Caspase-1 signaling pathway, which provides a new perspective and strategy to prevent liver injury induced by BaP.